Accurate lattice parameter measurements of stoichiometric uranium dioxide - Leinders, Gregory; Cardinaels, Thomas; Binnemans, Koen; Verwerft, Marc (Journal of nuclear materials, 2015)
•The lattice parameter of stoichiometric uranium dioxide has been re-evaluated.•The new value is substantially higher than the generally accepted value.•The new value has an improved precision.•Earlier published values on the lattice parameter of UO2 are carefully re-assessed.•High accuracy was obtained on both stoichiometry and lattice parameter measurements. The paper presents and discusses lattice parameter analyses of pure, stoichiometric UO2. Attention was paid to prepare stoichiometric samples and to maintain stoichiometry throughout the analyses. The lattice parameter of UO2.000±0.001 was evaluated as being 547.127±0.008pm at 20°C, which is substantially higher than many published values for the UO2 lattice constant and has an improved precision by about one order of magnitude. The higher value of the lattice constant is mainly attributed to the avoidance of hyperstoichiometry in the present study and to a minor extent to the use of the currently accepted Cu Kα1 X-ray wavelength value. Many of the early studies used Cu Kα1 wavelength values that differ from the currently accepted value, which also contributed to an underestimation of the true lattice parameter.